Against magical thinking regarding bibliometrics - Robinson-García, Nicolás (Anuario ThinkEPI, 2022)
This work discusses the current debate between the use of qualitative approaches versus the use of quantitative indicators in research evaluation. It argues that too much importance is currently given to the methods and criteria employed in evaluation instead of discussing the most essential issue: the goal that evaluation pursues and how different research activities are valued. To finish, some design problems of the Spanish research evaluation system are highlighted because those problems act as a barrier towards a more contextualized and responsible evaluation system.
Keywords: Research evaluation; Impact Factor; Scientometrics; Responsible use of metrics